Designing Metaverse-Based Learning Environments for Elementary Education in Europe - Müller, Sofia; Rossi, Luca (CV TOPAZART, 2025)
This paper explores the design and evaluation of a metaverse-based learning platform tailored for elementary schoolchildren in Europe. With immersive technologies such as virtual reality (VR) and augmented reality (AR) gaining traction in education, this study examines student engagement, usability, and perceived learning outcomes. A mixed-methods approach involving 240 students (aged 8–11) and 30 teachers across five European countries was employed. The findings reveal high levels of engagement (87%), moderate technical barriers, and positive teacher perceptions of pedagogical potential. The paper concludes with design recommendations and policy considerations for broader adoption.